Pengaruh Profitabilitas, Ukuran Perusahaan dan Opini Audit terhadap Audit Report Lag pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-202 - Astuti, Intan Novia; Ridha, Ainul (SI-MEN, 2024)
This study aims to determine the profitability, firm size and audit opinion on audit report lag in Banking Companies Listed on the Indonesia Stock Exchange in 2018-2022. The population in this study are Banking Companies Listed on the Indonesia Stock Exchange in 2018-2022. The sample collection method used purposive sampling method in order to obtain 23 companies that met the criteria as samples and obtained 115 observational data. The data analysis method used is multiple linear regression analysis. The results showed that simultaneously profitability, firm size and audit opinion affect audit report lag. Partially, Profitability affect audit report lag. Firm size and audit opinion have no effect on udit report lag.